2013
DOI: 10.5414/cp201777
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pharmacokinetics between sarpogrelate hydrochloride immediate-release formulation and controlled-release formulation

Abstract: After the administration of sarpogrelate hydrochloride CR and IR formulations using the same daily dose, AUCs were slightly higher for the CR formulation than for the IR formulation for both sarpogrelate and its metabolite M-1, but the C(max) values were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The mean C max of M‐1 was 48.4 ± 9.82 ng/mL at T max (1 h; range, 0.33–1.5 h), and the AUC 0–∞ values were 86.5 ± 7.80 ng·h/mL. The pharmacokinetic parameters of sarpogrelate and M‐1 were similar to those reported in the literature .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The mean C max of M‐1 was 48.4 ± 9.82 ng/mL at T max (1 h; range, 0.33–1.5 h), and the AUC 0–∞ values were 86.5 ± 7.80 ng·h/mL. The pharmacokinetic parameters of sarpogrelate and M‐1 were similar to those reported in the literature .…”
Section: Resultssupporting
confidence: 78%
“…Several methods have been developed for the determination of sarpogrelate using LC–MS/MS in human and rat plasma . In clinical pharmacokinetic reports of sarpogrelate, an LC–MS/MS method for the separate determination of sarpogrelate and M‐1 in human plasma has been described . This method requires two different sample preparation processes and an especially time‐consuming and laborious SPE procedure for the determination of M‐1, which limits its bioanalytical throughput capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In plasma protein-binding studies, the final concentrations of sarpogrelate or M-1 were both 0.5 and 10 mM. The LC-MS/MS conditions for determination of sarpogrelate and M-1 were optimized based on the conditions used in a previous study (Kim et al, 2013a).…”
Section: Methodsmentioning
confidence: 99%
“…After oral administration of 100 mg of sarpogrelate to healthy male subjects, sarpogrelate is rapidly absorbed from the gastrointestinal tract with a mean maximum plasma concentration (C max ) of 856.3 ng/mL at 0.7 hour and is rapidly eliminated from plasma with a half-life of 0.8 hour (Kim et al, 2013a). The active metabolite, M-1, reaches a C max of 49.3 ng/mL at 0.9 hour and exhibits slower elimination than sarpogrelate, with a half-life of 4.4 hours (Kim et al, 2013a). After absorption, sarpogrelate and M-1 further undergo glucuronide conjugations to form several metabolites, which are mainly excreted in bile (Kim et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in our previous study, the coefficient of variation (CV) for the C max of sarpogrelate was determined to be approximately 50%. Similarly, other studies have shown that it is 35% . In addition, most of the PK parameters reported for sarpogrelate are not from healthy Chinese subjects .…”
mentioning
confidence: 84%